Analisis Kemampuan Pemahaman dan Pemecahan Masalah pada Siswa Kelas VIII UPT SMP Negeri 27 Medan Terhadap Materi Bangun Datar dan Ruang - Siddik, Muhammad; Rizka. S, Nazwa; Jannah, Raudhatul; Fauzi, Muhammad Amin (LPPPI Publishing, 2024)
This study is a descriptive study with a qualitative approach that aims to analyze the errors made by students in solving mathematics problems, especially on flat and solid geometry materials using the Newman Theory approach. The subjects in this study were 30 seventh grade students at SMP Negeri 27 Medan. The method of collecting data or information was carried out through a written test of 3 (three) descriptive questions and interviews with selected subjects. The information obtained was then analyzed based on the Newman analysis procedure which is divided into 5 (five) stages of errors, namely reading, understanding, transformation, process skills, and writing answers. The results of the analysis showed that the most significant errors occurred at the transformation stage, with a percentage of 83.3%, categorized as very high. On the other hand, errors in process skills were classified as very low, namely 16.6%. This finding shows the importance of developing more effective learning methods to help students understand and solve mathematics problems, especially those related to geometric concepts.